2022
DOI: 10.1200/op.22.00143
|View full text |Cite
|
Sign up to set email alerts
|

Patient, Family, and Clinician Perspectives on Location of Death for Adolescents and Young Adults With Cancer

Abstract: PURPOSE: Adolescents and young adults (AYAs) with cancer have high rates of hospital deaths. It is not clear if this reflects their preferences or barriers to dying at home. METHODS: Between December 2018 and January 2021, we conducted in-depth interviews with AYAs (age 12-39 years) with stage IV or recurrent cancer, family caregivers including bereaved caregivers, and clinicians of AYAs with cancer. Patients were asked about their priorities for care including location of death, caregivers were asked what was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Previous work has identified the complexities faced by AYAs when considering hospice and location of death, including barriers to transfusions in hospice and concerns about the impact on young family members in the home. 28,29 Alternative models of care delivery, such as concurrent care available to children and adolescents or home hospice transfusion models, may better serve some AYAs, whereas for others, hospital-based care may best balance complex needs. 30,31 In addition, this study identified psychological and spiritual support as areas where supportive care can be maximized regardless of patient goals of care.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has identified the complexities faced by AYAs when considering hospice and location of death, including barriers to transfusions in hospice and concerns about the impact on young family members in the home. 28,29 Alternative models of care delivery, such as concurrent care available to children and adolescents or home hospice transfusion models, may better serve some AYAs, whereas for others, hospital-based care may best balance complex needs. 30,31 In addition, this study identified psychological and spiritual support as areas where supportive care can be maximized regardless of patient goals of care.…”
Section: Discussionmentioning
confidence: 99%
“…56 This is concerning because there is also evidence that AYAs with cancer prefer home-based, lessintense, or natural deaths. 43,57 The survival gap, high symptom burden, psychosocial and communication challenges, and concerns about goalconcordant care at the end of life make PC especially important for AYAs with cancer. One study suggests that oncology and PC clinicians agree that providing PC to AYAs with cancer can be particularly challenging.…”
Section: Aya Pc Needsmentioning
confidence: 99%
“…56 This is concerning because there is also evidence that AYAs with cancer prefer home-based, less-intense, or natural deaths. 43,57…”
Section: Aya Pc Needsmentioning
confidence: 99%
“…A fully informed and equipped workforce enables young people to live well with advanced cancer and also extends to improving the experiences of caregiver bereavement [52 ▪ ]. Addressing communication and relational challenges between T/AYAs, their parents, and their clinical teams, for example, could lessen the risk of complicated parental grief [17 ▪ ,53–55], and should be a component of pre-bereavement considerations [56].…”
Section: Implications For Practice and Suggestions For Future Workmentioning
confidence: 99%